Cadmium uptake and mycorrhization by cacao clones in agroforestry and monoculture systems of Peruvian Amazon (Bioagro, 2023)
The production system influences the cadmium (Cd) content and mycorrhization in cocoa plantations. The objective of this study was to determine the effects of different production systems on Cd uptake and the presence of mycorrhizas in cacao clones in field conditions, in the Peruvian Amazon. Twelve subplots of 108 m2 were selected in representative cocoa cultivation systems under agroforestry (AF) and monoculture (MON), with the cocoa clones ICS and CCN. Significant differences and data distribution were evaluated using ANOVA, principal component analysis, and Tukey's tests. Mycorrhizal colonization was higher in the AF_ICS system (71.11%) while the length of the extraradical mycelium was higher in the AF_CCN system (17.23%). The highest Cd content in soils was found under the AF_CCN and AF_ICS systems, both with 0.39 mg kg-1. The Cd content in cacao roots, leaves, and beans were higher in the MON_CCN system with 1.87, 2.06, and 1.12 mg kg-1 respectively. Cocoa monocultures (with both clones) generally showed lower levels of mycorrhizal colonization than agroforestry systems, which in turn (also for both clones) presented higher Cd content in beans, even exceeding the limit established by the world health authorities.
Keywords: Mycelium; mycorrhizal colonization; Peruvian amazon; Theobroma cacao